Contextual determinants influencing the implementation of fall prevention in the community: a scoping review - van Scherpenseel, M. C.; te Velde, S. J.; Veenhof, C.; Emmelot-Vonk, M. H.; Barten, J. A. (Frontiers in Health Services, 2023)
Background: Successful implementation of multifactorial fall prevention interventions (FPIs) is essential to reduce increasing fall rates in community-dwelling older adults. However, implementation often fails due to the complex context of the community involving multiple stakeholders within and across settings, sectors, and organizations. As there is a need for a better understanding of the occurring context-related challenges, the current scoping review purposes to identify what contextual determinants (i.e. barriers and facilitators) influence the implementation of FPIs in the community. Methods: A scoping review was performed using the Arksey and O’Malley framework. First, electronic databases (Pubmed, CINAHL, SPORTDiscus, PsycINFO) were searched. Studies that identified contextual determinants that influence the implementation of FPIs in the community were included. Second, to both validate the findings from the literature and identify complementary determinants, health and social care professionals were consulted during consensus meetings (CMs) in four districts in the region of Utrecht, the Netherlands. Data were analyzed following a directed qualitative content analysis approach, according to the 39 constructs of the Consolidated Framework for Implementation Research. Results: Fourteen relevant studies were included and 35 health and social care professionals (such as general practitioners, practice nurses, and physical therapists) were consulted during four CMs. Directed qualitative content analysis of the included studies yielded determinants within 35 unique constructs operating as barriers and/or facilitators. The majority of the constructs (n=21) were identified in both the studies and CMs, such as ‘networks and communications’, ‘formally appointed internal implementation leaders’, ‘available resources’ and ‘patient needs and resources’. The other constructs (n=14) were identified only in the studies. Discussion: Findings in this review show that a wide array of contextual determinants are essential in achieving successful implementation of FPIs in the community. However, some determinants are considered important to address, regardless of the context where the implementation occurs. Such as accounting for time constraints and financial limitations, and considering the needs of older adults. Also, broad cross-sector collaboration and coordination are required in multifactorial FPIs. Additional context analysis is always an essential part of implementation efforts, as contexts may differ greatly, requiring a locally tailored approach.